Application of mesotrione and atrazine in post-emergence of sorghum crop - Magalhães, Henrique Fernando de; Corrêa, Fernando Rezende; Silva, Nelmício Furtado da; Cavalcante, Wendson Soares da Silva; Ribeiro, Daniele Ferreira; Rodrigues, Estevão (Brazilian Journal of Science, 2023)
Assuming the sorghum crop has a limitation regarding the management of weeds, in addition to the scarcity of herbicide molecules that can be used in the management of weeds in the sorghum crop without causing damage to the crop or causing phytotoxicity that can drastically reduce crop development and sometimes lead to plant death, the aim of this study was to evaluate the phytotechnical effects on sorghum crop after application of isolated mesotrione and associated with an atrazine. The experiment was carried out at the Teaching, Research and Extension Farm at UniBRAS College - Rio Verde - GO, in a Red Distroferric Oxisol (LVDf). The experimental design used was a randomized block, with 8 treatments and 4 replications, a total of 32 experimental plots. The treatments consisted of using different models between the herbicides Atrazine and Mesotrione. Stem diameter, plant height, leaf number, leaf length, leaf width, leaf area index at 28 and 35 days after application of the herbicides at the phenological stage between V4 and V6 and the chlorophyll index were evaluated a, be total at 7 and 14 days after herbicide application. Data were discovered by analysis of variance (p < 0.05) and cases of significance were identified by Scott-Knott mean test (p < 0.05), using the Sisvar® statistical software.